(untitled) (Nusantara Medical Science Journal, 2022)
Introduction: Chronic exposure to fuel oil can cause chemical burns to the olfactory epithelium, which can cause anosmia. This study aimed to compare mucociliary transport time and olfactory function between operator and non-operator officers at gas stations. Methods: This cross-sectional study was conducted from September to November 2020 and involved 40 subjects divided into two equal groups each consisting of 20 gas station operators and non-operators, respectively. The examination of mucociliary transport time was carried out by saccharin test, while the olfactory function was examined by assessing e olfactory threshold, discrimination, and identification (TDI) score using the Sniffin sticks test. Results: There was a significant difference in the mean mucociliary transport time and olfactory function between gas station operators and non-operators (P<0.001). In addition, there was also a significant correlation between the mucociliary transit time and olfactory function (p<0.05), with a strong negative correlation coefficient (r=-0.620). Therefore, the longer the mucociliary transit time, the gas station attendant’s olfactory function will decrease. Conclusion: mucociliary transport time and olfactory function in non-operator public gas station officers were better than operators, probably because inhalation of chemical pollutants induces the release of proinflammatory cytokines, chronic inflammation of the nasal mucosa results in impaired olfactory cells and mucin glands.